Evaluation of nickel electroless plating on mild steel - Mohd Ridzwan, Adnan (2010)
Nickel electroless plating on mild steel is carried out by a chemical reaction and without the use of an external source of electricity. In nickel electroless plating, nickel chloride will come as a metallic salt and is reduced by using Sodium hypophosphite as the reducing agent to nickel metal, which then is deposited on the mild steel. In this experiment, the effect of solution concentration on thickness and mechanical properties of nickel plating on mild steel using electroless plating process was investigated. The solutions used in this experiment were Sodium hypophosphite and nickel chloride.with varying concentration. Electroless plating were done for 30 days. Then the surface structure and morphology nickel plating was evaluated using scanning electron microscopy (SEM), Optical Microscope while its hardness was evaluated using Vickers hardness test. In electroless plating, anode is the movements of negative ions toward the positive electrode and the mild steel as the cathode because the movement of positive ions toward the negative electrode. Electroless plating found the coating thickness by effected of percentage of concentration of solution, effect of thickness of coating to the mechanical properties and anode and cathode weight loss in electroless plating. The size of sample specimen is 0.05 m of length, 0.03 m of width and 0.001 m of thickness for both of mild steel and nickel sheet metal. The machine that was applied in the experiment were, shearing machine to cut the mild steel into size, drilling machine to make a hole to the surface of mild steel and nickel, micro vickers hardness test machine to get a mechanical properties behavior to mild steel after electroless plating and scanning electron microscopy (SEM) to get the microstructure observation of sample after electroless plating. The highest coating thickness is at 252 µm corresponding to percentage of concentration solution of 22.2 % at sample 8 followed by 19.4 %, 16.7 %, 13.9 %, 11.1 %, 8.3 %, 5.6 %, and 2.8 % for sample 7, 6, 5, 4, 3, 2, and 1. When the percentage of concentration of solution is increase, the hardness value of mild steel is decrease while the coating thickness increases. So, the grain size of microstructure will increase while increase the percentage of concentration of solution.